Investigating students' processes of noticing and interpreting syntactic language features in word problem solving through eye-tracking - Dröse, Jennifer; Prediger, S.; Neugebauer, P.; Danhier, R. D.; Mertins, B. (International Electronic Journal of Mathematics Education, 16(1), em0625)

Identifying obstacles is not enough for everybody – Differential efficacy of an intervention fostering fifth graders’ comprehension for word problems - Dröse, Jennifer; Prediger, S. (Studies in Educational Evaluation, 68 (100953))

Prokrastination bei Studierenden verringern durch Anwendung eines Ratgebers im Gruppensetting - Korsmeier, Teresa; Bobe, Julia; Klingsieck, Katrin B. (Zeitschrift für Beratung und Studium)

"Welcome to Night Vale" und/mit Derrida: Lernen, mit den Gespenstern zu leben? - Spener, Anna Maria (Literatur und das Böse. Beiträge des 10. Studierendenkongress Komparatistik)

"Meine Trauer war (k)eine Krankheit"? Achronologisches Erzählen einer anhaltenden Trauerstörung in Olga Grjasnowas "Der Russe ist einer, der Birken liebt" - Spener, Anna Maria (Anafora. Zeitschrift für Literaturwissenschaft)

A longitudinal analysis of the reciprocal relationship between academic procrastination, study satisfaction, and dropout intentions in higher education - Scheunemann, Anne; Schnettler, Theresa; Bobe, Julia; Fries, Stefan; Grunschel, Carola (European Journal of Psychology of Education)
Abstract Student dropout is a multi-causal process. Different theoretical models on student dropout consider dysfunctional study behavior (e.g., academic procrastination) and low study satisfaction as possible determinants of students’ dropout intentions during their university studies. However, these models neglect contemporary conceptualizations that assume reverse relationships between dropout intentions and other determinants of the dropout process. Until now, empirical evidence on these assumptions is scant. The present three-wave longitudinal study explored the reciprocal relationships between academic procrastination, study satisfaction, and dropout intentions over one semester. To this end, we used data of N = 326 undergraduate students enrolled in mathematics and law. Our latent cross-lagged panel model replicated existing empirical cross-sectional findings between the variables (i.e., academic procrastination, study satisfaction, and dropout intentions). Regarding the longitudinal relations, as expected, the cross-lagged effects showed that higher dropout intentions significantly related to subsequent higher academic procrastination and lower study satisfaction. Unexpectedly, academic procrastination did not significantly relate to subsequent dropout intentions. Additionally, higher study satisfaction significantly associated with subsequent higher dropout intentions—possibly due to unfulfilled expectations. Further, higher study satisfaction significantly related to subsequent higher procrastination—possibly due to more confidence among satisfied students. Our results broaden the view on dropout intentions as part of the dynamic interplay of student dropout determinants and the need to refine dropout models’ assumptions accordingly. Practically, realistic expectations seem important to reduce dropout intentions. Further, student counselors should have a closer look at the reasons for academic procrastination to develop individual solutions for this dysfunctional behavior.
Keywords: Developmental and Educational Psychology; Education

Digitales Praxissemester - kann das überhaupt gut gehen? - Göddertz, Nina (Care Work in der gesellschaftlichen Transformation. Beschäftigung, Bildung, Fachdidaktik)
Marianne Friese/Rita Braches-Chyrek Einführung Marianne Friese Care Work im Spannungsfeld gesellschaftlicher Transformation. Systemische Widersprüche und Entwicklungsperspektiven Berufliche Bildung und Beschäftigungssysteme Denise Becka und Michaela Evans Wohlfahrtsproduktion und Care im digitalen Wandel: Perspektiven für Beruflichkeit in der Pflege Heidrun Herzberg und Peter Alheit Zur Akzeptanz des Konzepts „Community Nurse" im Land Brandenburg: Eine qualitative Vorstudie Karin Reiber, Jan Braun und Jutta Mohr Berufliche Bildung in der Domäne Pflege zwischen Anforderungen des Beschäftigungssystems und individueller berufsbiografischer Entwicklung Philipp Struck Entwicklungs- und Verbesserungsperspektiven für berufliche (Aus-)Bildungsprozesse im Gesundheitswesen Rita Braches-Chyrek Soziale Arbeit: Ausbildung und Beschäftigung Julia Kastrup und Alexandra Brutzer Hauswirtschaft in Zeiten von Corona - Ergebnisse einer Interviewstudie mit Hauswirtschaftlichen Fachkräften Akademische Bildung und Weiterbildung Anna Bobe, Anke Karber und Tobias Moock Theorie und Praxis in sozialpädagogischen Bildungsgängen - Erste Strukturierungsansätze vielfältiger Verhältnisse Manuela Liebig, Mirjam Chris und Annemarie Marx „Am Ball bleiben" - Sensibilisierung für aktuelle Herausforderungen der sozialpädagogischen Praxis durch Arbeitsanalysen im Lehramtsstudium für berufliche Schulen Anja Walter, Martin Fritzenwanker, Martin Karstädt Von Berufsfeldanalysen zum Unterricht - empirisches Material für die Bildungspraxis im Berufsfeld Gesundheit und Pflege nutzen Nina Göddertz „Digitales Praxissemester - kann das überhaupt gut gehen?" - Reflexionen von Lehramtsstudierenden vor und während des Praxissemesters in Zeiten der Covid-19-Pandemie Stephanie Spanu Systemrelevant(e) ausbilden. Berufliches Lehramt, Fachrichtung Sozialpädagogik und die berufliche Bildung: Der Fachkräftemangel als gesellschaftliche Aufgabe Julia Kastrup, Birgit Peuker, Marie Nölle-Krug und Simon Vollmer Gemeinsam innovativ! - Transformative Themenfelder in der lehramtsbezogenen Ausbildung der beruflichen Fachrichtung Ernährung- und Hauswirtschaft standortübergreifend lehren und lernen Ursula Walkenhorst, Annika Lara Schwarze Digitale Transformation in der Hochschullehre - Chancen und Grenzen für die Gesundheitsberufe Dana Bergmann und Astrid Seltrecht Weiterbildungsordnungsarbeit für Pflegeberufe Claudia Schepers, Johanna Krawietz und Jella Fuchs Kollegiale Beratung für die Kitteltasche
Keywords: Modernisierung personenbezogener Dienstleistungsberufe Aktueller Forschungsstand; Best Practice und Desiderata

A Comparison and Combination of Unsupervised Blind Source Separation Techniques - Boeddeker, Christoph; Rautenberg, Frederik; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)
Unsupervised blind source separation methods do not require a training phase and thus cannot suffer from a train-test mismatch, which is a common concern in neural network based source separation. The unsupervised techniques can be categorized in two classes, those building upon the sparsity of speech in the Short-Time Fourier transform domain and those exploiting non-Gaussianity or non-stationarity of the source signals. In this contribution, spatial mixture models which fall in the first category and independent vector analysis (IVA) as a representative of the second category are compared w.r.t. their separation performance and the performance of a downstream speech recognizer on a reverberant dataset of reasonable size. Furthermore, we introduce a serial concatenation of the two, where the result of the mixture model serves as initialization of IVA, which achieves significantly better WER performance than each algorithm individually and even approaches the performance of a much more complex neural network based technique.

Convolutive Transfer Function Invariant SDR Training Criteria for Multi-Channel Reverberant Speech Separation - Boeddeker, Christoph; Zhang, Wangyou; Nakatani, Tomohiro; Kinoshita, Keisuke; Ochiai, Tsubasa; Delcroix, Marc; Kamo, Naoyuki; Qian, Yanmin; Haeb-Umbach, Reinhold (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Open Range Pitch Tracking for Carrier Frequency Difference Estimation from HF Transmitted Speech - Schmalenstroeer, Joerg; Heitkaemper, Jens; Ullmann, Joerg; Haeb-Umbach, Reinhold (29th European Signal Processing Conference (EUSIPCO))